Correlation and thermodynamic analysis of solubility of cefmetazole acid in three (alcohol + water) binary solvents at temperatures from 278.15 K to 303.15 K. (December 2016) - Sun, Mengmeng; Li, Kangli; Du, Shichao; Liu, Yumin; Han, Dandan; Li, Xiaona; Yang, Peng; Liu, Shiyuan; Gong, Junbo
Highlights: The solubility data of cefmetazole acid in three (alcohol + water) binary solvents were experimentally determined. The experimental solubility data of cefmetazole acid were correlated by three models. Almost all studied solutions show good agreement with the "like dissolves like" empirical rule. Thermodynamic properties of cefmetazole acid of mixing process were calculated and discussed. Abstract: The solubility of cefmetazole acid in binary solvent mixtures, (methanol + water), (ethanol + water) and (isopropanol + water), was determined by UV spectroscopic method at temperatures from 278.15 to 303.15 K. The solubility of cefmetazole acid increased with the increase of temperature in all solvents. In (methanol + water) co-solvent mixture, the solubility of cefmetazole acid is maximal in neat methanol. In (ethanol + water) and (isopropanol + water) solvent mixtures, the solubility of cefmetazole acid reaches its maximum when the mole fraction of alcohol is 0.5 and 0.4, respectively. The modified Apelblat equation, the CNIBS/R-K model and the Jouyban–Acree model were applied to correlate the experimental solubility of cefmetazole acid. Moreover, the activity coefficients as well as the thermodynamic properties of mixing were calculated and discussed based on the NRTL model and experimental solubility values.